Motivasi Petani Menggunakan Padi Varietas Baru Hasil Riset Badan Tenaga Nuklir Nasional Di Kecamatan Karangdowo Kabupaten Klaten - Refiana Wanda Sari; Sugihardjo Sugihardjo; Suminah Suminah (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2021)
Various types of rice are developed to increase crop productivity. The BATAN rice variety is a new variety of research results from BATAN or the National Nuclear Energy Agency. BATAN rice is produced from the development of nuclear technology by irradiating gamma radiation so as to produce rice with various characteristics .This study aims to determine the characteristics of farmers. Knowing the motivating factors and analyzing the motivating factors with the ERG (Existence Relatedness Growth) motivation of farmers using new varieties of rice from BATAN research. Research with quantitative methods. The location selection was made deliberately in Karangdowo District, Klaten Regency as an area where BATAN is located. The sampling technique was proportional random sampling with the Taro Yamane formula as many as 82 farmers. The data analysis used was the Spearman rank correlation test with the SPSS program. The results of the study: (1) the characteristics of farmers based on gender, the majority of men and 81 respondents, based on side jobs, the majority did not have side jobs, as many as 67 farmers and based on formal education the majority of education was very low 37 farmers. (2) motivating factors include age, non-formal education, the role of farmer groups, land area and intensity of extension workers. (3) Farmer's ERG motivation was in the high category, age and intensity of extension were significant. Non-formal education, land area and the role of farmer groups are not significant.